2020
DOI: 10.1002/adom.202001065
|View full text |Cite
|
Sign up to set email alerts
|

Transmission‐Reflection Controls and Polarization Controls of Electromagnetic Holograms by a Reconfigurable Anisotropic Digital Coding Metasurface

Abstract: Digital coding metasurface, which provides a new approach to link the physical world and information science, has been quickly developed in recent years. However, all previously reported metasurfaces cannot achieve independent controls of different polarizations in both transmission and reflection spaces at the same time. In this work, a reconfigurable anisotropic digital coding metasurface loaded with electronically controlled PIN diodes is proposed that can independently manipulate not only the near/far‐fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 58 publications
0
44
0
Order By: Relevance
“…A kind of reconfigurable anisotropic holographic metasurfaces was proposed to control independently the transmission and reflection modes of the EM waves under different polarizations. [32] Interestingly, fullstate synthesis of EM fields was proposed by using high efficiency phase-only metasurfaces. [33] More recently, Qu et al demonstrated a re-programmable metasurface that can produce arbitrary holographic images for optical encryption.…”
Section: Electromagnetic Holographymentioning
confidence: 99%
“…A kind of reconfigurable anisotropic holographic metasurfaces was proposed to control independently the transmission and reflection modes of the EM waves under different polarizations. [32] Interestingly, fullstate synthesis of EM fields was proposed by using high efficiency phase-only metasurfaces. [33] More recently, Qu et al demonstrated a re-programmable metasurface that can produce arbitrary holographic images for optical encryption.…”
Section: Electromagnetic Holographymentioning
confidence: 99%
“…Due to the sub-wavelength characteristics of metasurface elements, holographic images with high resolution are achieved, as shown in Figure 8c. Another p-i-n diode loaded reconfigurable anisotropic has been proposed to independently control not only the near/far-field pattern but also the reflection and transmission modes of different incident electromagnetic wave polarizations, as shown in Figure 8d [123]. Both the numerical simulations and experimental measurements show that different holographic images can be achieved under vertical and horizontal linear polarizations, respectively, and that operation in the transmission mode or reflection mode can be controlled in real-time.…”
Section: Reconfigurable Metasurface Hologramsmentioning
confidence: 99%
“…Then, differently polarized converters have been proposed based on the metasurface. Some works were proposed to realize LP to CP for the entire microwave frequency band, [22][23][24][25][26] while others can achieve polarization conversion within terahertz band (THz). [27][28] For enhancing the conversion bandwidth, various metasurfaces have been designed to manipulate the polarizations of transmissive waves.…”
Section: Introductionmentioning
confidence: 99%